THE EFFECT OF CBR VALUES ON THE SUBGRADE LAYER ON RUTTING DEPTH ON FINE CRACKS IN ASPHALT PAVEMENTS - Amalia, Rizki; Arifin , Syamsul; Nurdin, Sukiman (Prodi Teknik Sipil, Fakultas Teknik, Universitas Jember dan Forum Studi Transportasi antar Perguruan Tinggi, 2023)
Problems in the basic soil layer, which is generally sandy soil will greatly affect the life of the planned cracking and rutting in the construction of the paved layer. The purpose of this study was to determine the effect of CBR values on the Subgrade layer on the life of the paved road pavement plan until there began to be a fine crack on the paved road surface and predict the depth of rutting on the road surface when fine cracks began to occur. The method used in this study is the Determination of TYN and RDM Values using the HDM III. Based on the results of the analysis, it can be seen that the higher the CBR value, the longer it takes for a pavement to experience fine cracks as well as at the life of plans of 10, 15, and 20 years where the CBR value is directly proportional to the length of time a fine crack occurs. Predicted intensity of rutting (Decrease) at the time of the fine crack at the age of the 5-year plan, there was a decrease of 3.01 mm after 8.14 years of the road being opened. At the age of the 20-year plan, the value decreased by 2.33 mm after 5.438 years of the road being opened.